Outreach focused enterprise network workshop - Choi, Seoyeon (Nanyang Technological University, 2024)
This research focuses on aiding high school graduates in navigating their future academic paths by introducing them to the opportunities available at Nanyang Technological University’s School of Electrical and Electronic Engineering (NTU EEE) through interactive educational workshops. The workshops encompass a range of topics that provide participants with valuable exposure to Principles of Network (LAN, WAN, common devices), Network Communication and Protocols (IPv4 and IPv6 Address, OSI Model, TCP/IP Suite, HTTP, SMTP, and FTP), the Internet, and Network Security (Firewall, VPN, and Virtual LAN, and Port Security, and Access Control List), providing students with interesting but crucial insights into the field. Beyond delivering theoretical knowledge, workshops emphasize hands-on experience through laboratory sessions using Cisco Packet Tracer. This approach not only educates but also excites students about the possibilities in electrical and electronic engineering, fostering a proactive learning environment which make NTU EEE remain competitive.